172k views
4 votes
Prove the identity 2(sin⁶theta + cos⁶theta) - 3(sin⁴ + cos⁴theta) + 1 = 0​

User Rath
by
5.0k points

1 Answer

4 votes

Answer:

LHS=2(sin

6

θ+cos

6

θ)−3(sin

4

θ+cos

4

θ)+1

=2{(sin

2

θ+cos

2

θ)

3

−3sin

2

θcos

2

θ(sin

2

θ+cos

2

θ)}−3(sin

2

θ+cos

2

θ)

2

−2(sin

2

θcos

2

θ)}+1

We know, [sin²x+cos²x=1]

=2{1−3sin

2

θcos

2

θ}−3{1−2sin

2

θcos

2

θ}+1

=2−6sin

2

θcos

2

θ−3+6sin

2

θcos

2

θ+1

=0

=RHS

Explanation:

User Warkaz
by
4.4k points